1981
DOI: 10.1111/j.1151-2916.1981.tb10264.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Experimental Erosion Data with Elastic‐Plastic Impact Models

Abstract: Five target materials of varying mechanical properties were eroded with natural quartz sand and S i c particles. The targets were four commercially available Si3N, materials and MgF,. Several particle size ranges between 10 and 1000 pm. accelerated to several velocities between 61 and 275 m/s, were used for erosion testing. The erosion results are presented in terms of two models which have been developed for elastic-plastic impact damage. ECENT investigations have shown that R a number of erosion mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…(8), relative to the square root dependence in strength equations). Furthermore, the scatter in erosion data is such that it is difficult to distinguish between different theories (Gulden, 1981;Wiederhorn & Hockey, 1982). Nevertheless, all such theories lead to more or less the same main conclusions, that the wear rate increases with particle kinetic energy and diminishes with material toughness, as intuitively expected.…”
Section: E R O S I V E W E a Rmentioning
confidence: 92%
“…(8), relative to the square root dependence in strength equations). Furthermore, the scatter in erosion data is such that it is difficult to distinguish between different theories (Gulden, 1981;Wiederhorn & Hockey, 1982). Nevertheless, all such theories lead to more or less the same main conclusions, that the wear rate increases with particle kinetic energy and diminishes with material toughness, as intuitively expected.…”
Section: E R O S I V E W E a Rmentioning
confidence: 92%
“…For contacts in impact loading, Pi can be eliminated in favor of incident kinetic energy U i (via an appropriate contact equation) [58] to obtain an erosion equation. The most important predictions of this model, concerning the manner in which the removal rate increases with contact load or energy and decreases with material toughness, have been confirmed in extensive experimental studies on erosive wear in brittle glasses and ceramics [66][67][68][69].…”
Section: Erosive Wear and Machiningmentioning
confidence: 88%
“…Of the crack systems discussed in sections 2 and 3 it is the lateral which constitutes the most effective chipping mode [1] (although the cone crack can also be effective in this regard, especially when overlap between adjacent contact sites is frequent). These removal processes can be either highly deleterious or highly beneficial, depending on whether one is seeking to minimize or to maximize the removal process; that is, whether one is concerned with erosive wear [66][67][68][69] or with machining [70J properties.…”
Section: Erosive Wear and Machiningmentioning
confidence: 99%
“…Finnie [27] studied the effect of spherical particles on brittle materials and reported that the velocity and impact angle of particles are the primary factors for the erosion of brittle materials, although he stated that to a different degree, particle size, shape, hardness, and strength are also important. Gulden [32,33] studied the effects of soft silica particles on silicon nitride. The author observed that no lateral fracture propagated due to impact and, therefore, suggested that the energy of the particle changed to the plastic deformation of the particles themselves and erosion was due to minor chipping.…”
Section: Model Formulationmentioning
confidence: 99%